Hearing in workers exposed to low-dose radiation for a long period - Karlidag, T; Kaygusuz, I; Keles, E; Yalçin, S; Serhatlioglu, SS; Açik, Y; Öztürk, L (Elsevier Science Bv, 2004)
The aim of the present study was to evaluate changes in hearing thresholds with standard and high frequency audiometry in workers exposed to low-dose ionizing radiation for a long period. A total of 57 (49 male and 8 female) technical staff working in radiology-related jobs who were exposed to occupational radiation were included in the study. The control group consisted of 32 (27 male and 5 female) volunteer subjects with normal hearing. The symptoms like tinnitus, vertigo, weakness and lack of appetite were evaluated. A standard ascending/descending method was applied to the subjects of the study and the control groups in order to determine their hearing thresholds at eleven different frequencies between 250 and 16 000 Hz. In the study group, the working duration of subjects ranged from 4 to 23 years, and the percentage of tinnitus, weakness, vertigo and lack of appetite were 47%, 28%, 24% and 17%, respectively. It was observed that pure tone hearing thresholds were markedly increased for 4000, 6000, 8000, 14 000 and 16 000 Hz frequencies in the study group compared to the control group (p < 0.01). Levels of static compliance and middle ear pressures of the study group were similar to the control group. Tinnitus, vertigo and hearing loss in high frequencies were observed in the subjects exposed to the radiation for a long period. Subjects under high risk should be evaluated periodically. We suggest that the use of standard and high frequency audiometry together could be beneficial in the evaluation of these subjects. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: high-frequency audiometry; hearing loss; radiation